A Lightweight One Time Password (OTP) Based Smart Learning in Internet of Things - Rao Kadham, Nithin; Ravi.K, Sreenivasa (International Journal of Engineering and Technology, 2018)
The Internet of Things is another worldview that is changing processing. It is expected that all items around us are associated with the system, giving "whenever, anyplace" access to data. This idea is making progress, because of advances in nanotechnology which permits the making of gadgets fit for interfacing with the Internet productively. Presently a day countless are associated with the web, running from cell phones to machines. In this paper we concentrate on the instruction field, this paper manages the use of the ideas of Internet of Things and its application in making brilliant condition. The particular objective is to plan a keen situation for upgrading the instructing and learning forms at colleges. The earth ought to incorporate sufficient ideas of keen structures and brilliant classrooms with e-learning frameworks, to furnish understudies with cutting edge e-learning administrations and administrations that enhance the general nature of understudies' understanding. In this paper, we have proposed a safe biometric, One Time Password (OTP) and ace key based validation framework in IoT organize. The confirmation convention utilizes XOR operation and lightweight hash operation. The security examination demonstrates that it is safe against various assaults.Â